(3GdeNJGQ ef GdCfS GdLdjd HJGQjN GdbOS hGdNdjds - (3YHO GdQMef Hf eMeO Hf YHO GdQMef GdoYndrjej GdMfHdj, nCoHh Gdojref, eLjQ GdOjf,J (B928 (3g` s
(3ChdgG (B:s
(3eG GNJQJ fbdg ef JGQjN GdCfS GdLdjd GdTjN GdEeGe GdYGde bGQF GdMOjK GdTQja HHjJ GdebOS s
(3BNQgG (B:s
(3adeG SLO Jhai ai SLhOg aZSd ef hbJg hLF Hg Edi GdeSLO GdCbUi hUdi YdjgeG eYG hMedG Edi eG edG hOafG gPG BNQ eG GNJQJ fbdg ef JGQjN GdCfS GdLdjd hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B176 - (3U(B183s
(3HgG fXGe GdJYbjHIs
(3ai GdeYgO fSNI ef GdCf SGdLdjd HQbe (B69 (3JGQjNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B177s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B170 s
Keywords: (3GdJGQjNs